VIBRATIONAL-RELAXATION OF NCO(X) BY RARE-GASES, AND RATE-CONSTANT MEASUREMENT OF THE NCO + NO REACTION - Hancock, G; Mckendrick, K (1986)
Vibrational relaxation of the v2 mode of NCO(X̃) by rare gases takes place at rates which are in the order Ne < He ≈ Ar < Kr. The bimolecular rate constant for the NCO + NO reaction is (3.4±0.3)×10-11 cm3 molecule-1 s-1 at 295 K. © 1986.